Does Leadership Effectiveness Matter for Indonesia Vocational Teacher Performance? The Mediating Role of Work Motivation - Etta Mamang Sangadji; Sopiah Sopiah; Bagus Shandy Narmaditya (Universitas Jambi, Indonesia, 2021)
Enhancing teacher performance is a global challenge and understanding managerial sides, and motivation can be used to deal with this issue. The purpose of this study aimed at examining the impact of leadership effectiveness and teacher performance in vocational school, as well as investigating the role of work motivation. A quantitative method was adopted to improve understanding of this phenomenon. The participants of this study were recruited from the vocational school teachers in East Java by distributing online questionnaires employing WhatsApp. The findings of this study showed that effective leadership positively influenced both work motivation and teacher performance. Indeed, work motivation can explain the relationship between effective leadership and vocational teacher performance. Based on the results, it is recommended to the education office, school principals, vocational teachers to pay more attention to the effectiveness of leadership, and work motivation to improve teacher performance. This study recommends that school principals and educational policymakers pay attention to the matters of leadership and work motivation as the essential factor in driving teacher performance.